Clan and Tribal Perspectives on Social, Economic and Environmental Sustainability : Indigenous Stories from Around the Globe - Spee, James C.; McMurray, Adela; McMillan, Mark David, 1969- (Emerald Publishing Limited, 2021)
In a climate of in-migration, clan and tribal communities have been forced to build sustainable solutions together. Breaking fresh ground by shining a light on sustainability journeys from outside the global mainstream, this book demonstrates how sustainable development occurs in respectful collaboration between equals.